Investigation of the effect of para-amino benzoic acid (PABA) added starch-coated chemicals on the printability properties of paper - ÖZCAN, ARİF (SAGE PUBLICATIONS LTD, 2019)
Introduction: Paper is the most important material of the printing industry and is being improved due to the increasing needs of industry. The most important process to improve the optical and physical properties of paper is the surface coating. Paper has a smoother and opaquer surface with surface coating. In addition, brightness, whiteness, and yellowness values are improved with surface coating. Ultraviolet (UV) light in sunlight causes changes in the structure of the paper and coating chemicals and accordingly causes yellowing. Para-amino benzoic acid (PABA), due to its chemical structure, is a UV-blocking agent used in sunscreen creams. Methods: The effect of PABA on paper gloss, yellowness, and lightfastness values was investigated by adding it into the surface coating formulation. For this purpose, coating formulations were prepared with cationic starch and 3%, 5%, and 7% PABA; coatings were applied to the paper according to laboratory condition standards. Coated papers were printed with an IGT-C1 lab-type offset printability device with magenta ink. The printed papers were then exposed to a light fastness test with Solarbox. The color, brightness, and yellowness values of all samples before and after lightfastness were measured with an X-Rite spectrophotometer. The gloss of coated and printed paper sample values was measured with a BYK-Gardner glossmeter. Results: The gloss values of paper to which PABA was added, increased; however, it was determined that these gloss values decreased after the lightfastness test. Conclusions: PABA-added cationic starch coatings are more affected by UV light than cationic starch coatings.
Keywords: Para-amino benzoic acid; paper coating; lightfastness; yellowness; gloss; LIGHT FASTNESS; INK; PAPERMAKING